Anatomical study and clinical significance of the posterior ramus of the spinal nerve of the lumbar spine - Zhang, Zhenfeng; Liu, Jing; Xu, Yejie; Chen, Zeyan; Luo, Shiwen; Zhang, Xin; Wang, Guoliang; Cheng, Liang (Frontiers in Cell and Developmental Biology, 2022)
Background and objectives: Chronic nonspecific back pain is a common clinical disease typically treated by ultrasound-guided spinal injection. This minimally invasive treatment targets the posterior ramus of the spinal nerve (PRSN). The target of the medial branch is clear, but there is unclear target for the intermediate and lateral branches. This study attempted to observe the distribution of PRSN in the dorsal region of transverse process to provide a more detailed anatomical basis for treating spinal pain. Methods: The present study was conducted on 16 transverse processes of six adult male embalmed corpses. The dorsal area of the transverse process was divided into three equal zones, which are zone I, zone II and zone III from inside to outside. The origin, distribution, quantity, transverse diameter, and relationship with the bone structure of the PRSN on the transverse process were observed. Results: Sixty PRSNs were found in the lumbar of six cadavers, of which 48 were divided into three branches, and 12 PRSNs were divided into two branches. The intermediate branch is mainly distributed in zone I, and the lateral branch is mainly distributed in zone II. Twenty-nine communicating branches were found in 48 adjacent segments of six specimens, all of which originated from the intermediate branch of the previous segment and connected with the lateral branch of the next segment. Conclusion: This anatomical study describing the PRSN may have important clinical significance for spinal surgeons. Understanding the bony localization targets of the PRSN and the links between the PRSNs may benefit patients with low back pain who receive spinal injections.